Exposure and response to methyl isocyanate: results of a community based survey in Bhopal. Issue 7 (July 1988) - Andersson, N; Kerr Muir, M; Mehra, V; Salmon, A G
Abstract : In the two weeks immediately after the Bhopal disaster a community based survey was carried out in a series of eight exposed and two non-exposed clusters of households. The primary concern was the effect of the gas (subsequently identified as methyl isocyanate) on the eyes of the victims but data were also sought on respiratory status and the first symptoms of the exposure. No case of blindness was encountered that could be attributed to the gas. The most frequent symptoms reported were burning of the eyes, coughing, watering of the eyes, and vomiting. Among these, the frequency of cough most closely followed the rate of death in the different clusters. Although much rarer overall, the frequency of reported diarrhoea appeared to bear a stronger relation to death rates. Reports of photophobia and the clinical finding of superficial interpalpebral erosion of the cornea were more frequent where the death rates were lower. This clinical and epidemiological picture is consistent with different effects of the gas at different doses (as estimated from distance from the factory).